Aspidistra viridiflora (Asparagaceae, Nolinoideae), a new species from Vietnam - Vislobokov, Nikolay A.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Romanov, Mikhail S.; Nuraliev, Maxim S. (Phytotaxa, 2017)
One following the news of systematics of the genus Aspidistra Ker Gawler (1822: 628) should notice that the year 2016 brought us at least 16 new taxa, including 15 new species and one subspecies (Averyanov & Tillich 2016, Averyanov et al. 2016, Liang et al. 2016, Liu et al. 2016, Ly & Tillich 2016, Pan et al. 2016, Tanaka 2016, Vislobokov 2016, Vislobokov et al. 2016a, 2016b, Zhou et al. 2016). Indeed, Aspidistra is a large and rapidly growing genus which comprises about 160 species, including more than 60 of them known in Vietnam (e.g., Tillich 2005, 2008, 2014, Averyanov & Tillich 2015, 2017, Colin 2015, Vislobokov 2015, 2016, Averyanov et al. 2016, Vislobokov et al. 2016a, 2016b).